Myelodysplastic syndromes (MDS): prognostic factors and scoring systems - Souto, Elizabeth Xisto [UNESP] (1997)
OBJECTIVE: To evaluate the score systems of Cassano and Sanz and suggest a new one. DESIGN: Case series. LOCATION: Teaching hospitals: EPM UNIFESP and Faculdade de Medicina de Botucatu. PARTICIPANTS: 59 patients diagnosed from 1979 to 1992. INTERVENTION: Evaluation of clinical-laboratorial data. MEASUREMENT: Statistical comparison, uni and multivariate analysis and actuarial survival curves. RESULTS: Cassano's system divided the patients into high and low risk (p=0.0966) while, Sanz's gave high, intermediate and low risk (p=0.0108). The univariate analysis showed hemoglobin, WBC count, E/M ratio, liver size and blast percentage in BM as statistically significant. The multivariate analysis showed blast percentage in BM (p=0.004) and Hb (p=0.050) as significant. Our system, considering the multivariate analysis data, divided the patients into high, intermediate and low risk (p=0.0038). CONCLUSIONS: Sanz's system was more functional than Cassano's, while ours showed predictive survival value and ease of use in clinical practice.